Ciliogenesis is intrinsically altered in COPD small airways. Issue 6 (22nd December 2022) - Luczka-Majérus, Emilie; Bonnomet, Arnaud; Germain, Adeline; Lalun, Nathalie; Kileztky, Claire; Perotin, Jeanne-Marie; Deslée, Gaëtan; Delepine, Gonzague; Polette, Myriam; Dormoy, Valérian; Coraux, Christelle
COPD is characterised by a progressive and irreversible airflow limitation due to airway obstruction and emphysema [1]. We and others showed that bronchial epithelial remodelling in COPD is characterised by alteration of ciliogenesis and cilia function [2, 3], as well as a dysregulation of non-motile primary cilia (PC) [4]. In COPD, the main site of obstruction is in the small airways [5]. Considering that COPD is foremost a small airway disease (SAD) [6–8], we investigated the differentiation of bronchiolar epithelium in COPD, focusing on motile and primary ciliogenesis. An alteration of primary and motile ciliogenesis is detected in mild/moderate COPD small airways and could be at the origin of the initiation of epithelial remodelling http://bit.ly/3Tz3JDj